2010
DOI: 10.1111/j.1365-2605.2010.01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm morphology assessment using David’s classification: time to switch to strict criteria? Prospective comparative analysis in a selected IVF population

Abstract: The aim of this study was to compare assessment of sperm morphology by using David's classification (DC), a method of manual analysis most common in France, with a computer-assisted method (Integrated Visual Optical System) based on the strict criteria (CASA SC) for their ability to predict fertilization in a selected in vitro fertilization (IVF) population. A total of 120 couples engaged in IVF protocols were prospectively included in the study. To focus mainly on sperm morphology, couples were excluded in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
(66 reference statements)
0
23
0
1
Order By: Relevance
“…For sperm concentration and motility, French experts confirmed that the methods have not changed noticeably during the study period (Rolland et al 2013). Regarding morphology classification, a majority of the laboratories used David's classification during the study period (Blanchard et al 2011). …”
Section: Measurement Methodsmentioning
confidence: 88%
“…For sperm concentration and motility, French experts confirmed that the methods have not changed noticeably during the study period (Rolland et al 2013). Regarding morphology classification, a majority of the laboratories used David's classification during the study period (Blanchard et al 2011). …”
Section: Measurement Methodsmentioning
confidence: 88%
“…This is in contrast to the Shayeb et al (6) paper, where data were collected over 18 years. The use of a modified David classification (13,14) in our laboratory for morphology (18) is based on experience and constitutes a standard method in France (19), even if it does not really allow for international comparisons on morphology. However, all other sperm parameters were analyzed according to WHO manual (12) and can be compared.…”
Section: Discussionmentioning
confidence: 99%
“…A routine analysis included assessment of pH, semen volume (mL), sperm concentration (million/mL), total sperm count (million), percentage motility (overall and progressive), and percentage normal forms. Sperm morphology was assessed according to a modified David classification (13,14) after Harris-Schorr staining. Concentration and total sperm count were quoted as ''0'' in cases of azoospermia.…”
Section: Semen Analysismentioning
confidence: 99%
“…Subsequently the anomalies are classified using strictly defined criteria. By contrast, computer-assisted technology measures different morphological features (mostly head parameters) for each selected sperm cell (van der Horst et al 2009, Auger 2010, Bellastella et al 2010, Blanchard et al 2011, Butts et al 2011. Therefore, the parameters of normal sperm can differ according to staining method of sperm sample (Maree et al 2010).…”
Section: Evaluation Of Sperm Morphologymentioning
confidence: 99%